Investigating the effects of ebselen, a potential new lithium mimetic, on glutamate transmission. Issue 7 (3rd March 2020) - Mota, Filipa; Sementa, Teresa; Taddei, Carlotta; Moses, Natasha; Bordoloi, Jayanta; Hader, Stefan; Eykyn, Thomas; Cash, Diana; Turkheimer, Federico; Veronese, Mattia; Singh, Nisha
Abstract : Ebselen, a potential new lithium‐like drug, treatment reduced brain glutamate, as measured by PET imaging using the mGluR5 radioligand [ 18 F]FPEB in rats.